Maternal high-salt intake induces sex-specific liver injury in offspring: integrative transcriptomic and therapeutic investigation - Chen, Xiuli; Chen, Rui; Song, Wanyu; Wang, Li; Wu, Haiying (Frontiers in Nutrition, 2025)
IntroductionMaternal diet is a key determinant of fetal organ development, and excessive salt intake has been increasingly linked to long-term metabolic disorders. This study investigated the effects of maternal high-salt diet (HSD) on offspring liver health, with a focus on sex-specific structural and molecular alterations.MethodsPregnant C57BL/6J mice were fed either standard chow or an HSD (4% NaCl) during gestation and lactation. At 4 weeks of age, offspring livers were analyzed using histology, RNA sequencing, immunofluorescence, and biochemical assays. Connectivity Map (CMap) was applied to identify candidate therapeutic compounds.ResultsMaternal HSD significantly increased liver weight and hepatocyte size in offspring, with more pronounced effects in males. RNA sequencing identified 466 differentially expressed genes (DEGs) in males and 309 in females, indicating sex-dependent dysregulation of pathways related to metabolism, fibrosis, inflammation, and apoptosis. Masson's trichrome staining revealed increased collagen deposition, particularly in males, consistent with transcriptomic signatures of fibrosis. Immunofluorescence confirmed upregulation of apoptosis-related markers. CMap analysis identified potential therapeutic agents, including ketoprofen and BRD-K88741031, which alleviated HSD-induced hepatic injury in preliminary validation.DiscussionMaternal high-salt intake induces sex-specific structural and molecular liver injury in offspring, highlighting the developmental origins of liver disease. These findings emphasize the importance of maternal nutrition in shaping offspring hepatic health and suggest potential pharmacological strategies to counteract early-life dietary insults.